Sentidos e significados dos professores sobre os norteadores legais para o ensino de Química - Mendonça, Juliene Leonel de Almeida (2010)
This research aimed at understanding and analyzing the meanings and significances attributed by secondary school teachers to legal documents that guide the teaching of chemistry in high school. To do that, the work was exploited, from the legal guidings, the possible contradictions that there are in the implementation of education policies and, to a certain extent, these documents favor or create barriers to promote the changes in the school context. This research was anchored in historical and cultural theory of Vygotsky (1989, 1995, 2001). This study has qualitative character, which used semi-structured interview as a source of data collection that was conducted with secondary school chemistry teachers, who work in Stateowned school in a city of Triângulo Mineiro . The interviews were audio-recorded and accompanied by notes. Then they were heard and transcribed. The research results showed that most respondents did not know the legal guidings for secondary school deeply. Thus, the proposed reforms to education published in the legal guidings were not appropriate, they remain strange and little understood by teachers. However, teachers demonstrated, even modestly, be on a par of the discussions related to interdisciplinarity and contextualization. However, several obstacles were encountered to put these practices into action, such as work overload, lack of material resources, inappropriate physical infrastructure of schools, not enough number of classes per group, ill-prepared and insecure teachers; concern about fulfilling the curricular content proposed by legal guidings, inappropriate textbooks, lack of autonomy of teachers, repression and control of power by school administrators, the depreciation of the teacher, the discredit of the government's proposals, among others. The way teachers express themselves made it possible to understand the discouragement, hopelessness and degradation experienced by these professionals. By doing so, it was concluded that there is a rupture between meaning and significance of teaching activity, which makes the work of these professionals empty of meanings. This is due to the distance between what is proposed in the legal documents and school reality. This distance may decrease when educational policies involve the teachers both in the preparation and implementation of proposals for curriculum innovation.